Anisotropic wood-based cellulose dynamic self-adaptive hydrogel as well as preparation and application thereof
By constructing anisotropic wood-based cellulose dynamic adaptive hydrogel, combining cellulose frame modification and dynamic network structure, the contradiction between hydrogel materials in structural stability and dynamic nature is solved, and the cellular microenvironment is realized The simulation and tissue repair effects meet the needs of biological tissue engineering.
Patent Information
- Application Number
- CN202411182617.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2025-01-03
AI Technical Summary
There is a contradiction between structural stability and dynamics of existing hydrogel materials, which cannot effectively simulate the dynamic structure of the cellular microenvironment, and the dynamic adaptability is not enough to meet the needs of tissue repair.
Using anisotropic wood-based cellulose dynamic adaptive hydrogel, the cellulose frame is modified by removing hemicellulose and lignin, and the aldehyde functional groups are introduced, and the cellulose frame is oxidized by acrylamide free radical polymerization and oxidation of cellulose frame. Aldehyde groups form reversible covalent bonds, and combine ionic cross-linking of sodium alginate to construct a dynamic reversible network structure.
It realizes directional growth and transmission of cells, simulates the natural ECM microenvironment, improves the mechanical properties and biocompatibility of the materials, meets the stability needs of tissue repair, and solves the problem of low mechanical properties of dynamic hydrogels.
Smart Images

Figure CN119241915A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of medical materials, and particularly relates to an anisotropic wood-based cellulose dynamic adaptive hydrogel and a preparation method and application thereof. Background Art
[0002] Tissue engineering technology has a wide range of applications in the replacement and repair of damaged tissues or organs, research on disease pathogenesis, and drug screening. Hydrogels have physical properties similar to those of natural cytoplasmic matrix (ECM) and a three-dimensional hydrophilic porous network that can permeate nutrients. They can simulate many properties of natural tissues and provide a suitable environment for cell growth, proliferation, and differentiation, making them ideal materials for tissue engineering scaffolds.
[0003] Although there are many similarities between hydrogels and human biological tissues, compared with hydrogels in biological soft tissues, synthetic hydrogels lag behind biological systems in terms of structural accuracy, mechanical properties, and especially dynamic adaptability. Life systems in nature are constantly developing themselves, and dynamics, self-organization, and self-adaptation are their most important characteristics. Developing dynamic adaptive hydrogels similar to life systems for studying life-related phenomena is an important goal of hydrogel science at present. Currently, most common chemically synthesized hydrogels are formed by stable covalent cross-linking between polymer chains, which also determines that they are mainly composed of static polymer networks. Due to the lack of a good energy dissipation mechanism, the mechanical properties are often insufficient and this 2D static network structure may limit the interaction between cells and substrates, hindering the normal function of cells or tissues (for example, affecting cell diffusion and migration, or causing the failure of mitosis). The natural ECM of human soft tissue is a biomedical hydrogel with the best performance formed through millions of years of biological evolution. Many soft tissue ECMs (such as cartilage, skin, ligaments, etc.) choose highly ordered anisotropic structures to construct their load-bearing biological tissues. They not only have extremely excellent macroscopic biomechanical properties, but also have good microstructural dynamic properties, which can effectively support cell proliferation, migration, assembly, differentiation, development and other cell behaviors in the three-dimensional environment of ECM. Compared with the harder matrix of 2D static covalent hydrogels, dynamic hydrogels can provide a dynamic 3D culture matrix to simulate the rapidly changing microenvironment of natural ECM, allowing cell proliferation and differentiation. However, at present, dynamic adaptive hydrogels often have weak mechanical strength while maintaining good dynamic adaptability and cannot meet the needs of long-term implantation and repair.
[0004] Therefore, solving the contradiction between the structural stability and dynamics of current hydrogel materials and constructing a bionic dynamic adaptive hydrogel that has an anisotropic structure, good mechanical properties and can simulate the dynamic characteristics of the natural ECM microstructure has important practical significance for the development of the field of cartilage tissue repair engineering. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide an anisotropic wood-based cellulose dynamic adaptive hydrogel and its preparation and application. In particular, it relates to an anisotropic wood-based cellulose dynamic adaptive hydrogel with a reversible dynamic structure and a certain mechanical structural stability and its preparation method and application.
[0006] The present invention solves the problem that the current traditional hydrogel materials cannot simulate the dynamic structure of the cell microenvironment and the problem that the stability of the dynamic state hydrogel does not meet the needs of tissue repair, and constructs a bionic dynamic adaptive hydrogel with anisotropic structure, good mechanical properties and the ability to simulate the dynamic characteristics of the natural ECM microstructure, which has important practical significance for the development of the field of tissue repair engineering. The present invention provides a dynamic cellulose hydrogel that can adapt to the physiological activities of cells. The hydrogel removes the anisotropic cellulose framework of hemicellulose and lignin by delignifying wood. Then the cellulose framework is modified by sodium periodate, and the modified oxidized cellulose framework not only retains the anisotropic structure of the original cellulose framework, but also greatly widens the channel gap of the framework and introduces aldehyde functional groups. The original anisotropic structure can promote the directional growth and transmission of cells and various substances, and the larger channel can better promote the above effects. The introduced functional groups can form a dynamic structure with the amino-containing gel component to achieve the simulation of the dynamic microenvironment of the cell, thereby further promoting the tissue repair effect. Finally, the first cross-linked network is formed by free radical polymerization of acrylamide (AM) immersed in the oxidized cellulose framework and reversible covalent bonds of Schiff base formed by the aldehyde group of the oxidized cellulose framework and the amino group of acrylamide, and the second cross-linked structure of calcium ions and sodium alginate (SA) is formed in the gel through ionic cross-linking.
[0007] The anisotropic cellulose skeleton in the structure is similar to the collagen fiber structure, providing mechanical support; the gel component is similar to the highly absorbent proteoglycan in ECM, simulating the biological dynamic microenvironment; the modified cellulose framework and polyacrylamide are linked by reversible Schiff base bonds, and the ionic bonds of sodium alginate provide a second reversible cross-linking. This structure is similar to the dynamic network between glycosaminoglycans and collagen fibers, achieving the combination and synergy between structures, and simulating the structural component characteristics of natural ECM to the greatest extent. Through this method, the dynamic adaptive network is combined with the anisotropic structure, which can not only promote the directional growth of cells in the hydrogel network, but also solve the problem of low mechanical properties of dynamic hydrogels to a certain extent. It provides a unique solution to the scientific problem of balancing the structural stability and network dynamics of dynamic adaptive hydrogels, and provides a new solution for the application of hydrogels in the field of biological tissue engineering.
[0008] The present invention provides an anisotropic wood-based cellulose dynamic self-adaptive hydrogel, wherein the anisotropic wood-based cellulose dynamic self-adaptive hydrogel components include an oxidized cellulose framework and a gel precursor containing amino groups, which react under initiator conditions to form a chemical and reversible cross-linked network;
[0009] Or the anisotropic wood-based cellulose dynamic adaptive hydrogel components include an oxidized cellulose framework, an amino-containing gel precursor, and sodium alginate, wherein the hydrogel contains an oxidized cellulose framework and an amino-containing gel precursor that react under initiator conditions to form a chemical and reversible cross-linked network, and the sodium alginate forms an ionic cross-linked network through ionic cross-linking.
[0010] The Schiff base bonds formed between the aldehyde groups of the oxidized cellulose and the amino groups of the gel precursor acrylamide containing amino groups and the ionic bonds in the sodium alginate network construct a dynamic reversible network, simulating the dynamic microenvironment of cell growth.
[0011] The oxidized cellulose framework is an anisotropic oxidized cellulose framework, which simulates the anisotropic structural characteristics of human tissues such as cartilage and muscle.
[0012] Preferably, the gel precursor containing amino groups is acrylamide.
[0013] The present invention provides a method for preparing anisotropic wood-based cellulose dynamic adaptive hydrogel, comprising method 1 or method 2:
[0014] Method 1: A gel precursor containing amino groups, an initiator, and water are mixed to obtain a mixed solution, an oxidized cellulose framework is added, and then the gel precursor is fully filled into the cellulose framework by vacuum impregnation, and a heat treatment is performed to fully cross-link the acrylamide to obtain an anisotropic wood-based cellulose dynamic adaptive hydrogel, wherein the gel precursor containing amino groups is acrylamide;
[0015] Method 2: Mix a gel precursor containing amino groups, an initiator, and sodium alginate to obtain a mixed solution, add an oxidized cellulose framework, and then vacuum impregnate to fully fill the gel precursor into the cellulose framework, heat treat to fully cross-link the acrylamide, and then vacuum impregnate and soak in an ionic solution to obtain an anisotropic wood-based cellulose dynamic adaptive hydrogel, wherein the gel precursor containing amino groups is acrylamide.
[0016] Preferably, the preparation method of the oxidized cellulose framework in methods 1 to 2 comprises: reacting wood in a mixed solution of sodium hydroxide and sodium sulfite, washing, then soaking in a sodium hypochlorite solution until the wood turns white to obtain white wood, placing the white wood in a sodium periodate solution to react, washing, and obtaining the oxidized cellulose framework.
[0017] Preferably, the wood includes at least one of basswood and balsa wood; the concentration of sodium hydroxide in the mixed solution of sodium hydroxide and sodium sulfite is 1-5 mol / L, and the concentration of sodium sulfite is 0.1-1.5 mol / L; the mass ratio of the mixed solution to the wood is 100:5-20; the mass percentage concentration of the sodium periodate solution is 0.5-5wt.%.
[0018] Preferably, the wood is reacted and washed in a mixed solution of sodium hydroxide and sodium sulfite, wherein the reaction temperature is 85-100° C. and the time is 3-5 hours; the washing is 3-5 times of deionized water washing;
[0019] Preferably, the white wood is placed in a sodium periodate solution for reaction and washing, wherein the reaction temperature is 20-50° C. and the time is 3-12 hours; the washing is performed using ethylene glycol and 2-3 times of deionized water.
[0020] Preferably, the initiator is an initiator that can initiate free radical polymerization of acrylamide, and further, the initiator includes at least one of ammonium persulfate and Irgacure 2959; the mixed solution also includes a crosslinking agent, and the crosslinking agent is a crosslinking agent that crosslinks polyacrylamide, wherein the crosslinking agent includes at least one of N, N'-methylenebispropionamide and polyisomethacrylate;
[0021] Preferably, the concentration of acrylamide in the mixed solution is 10-40wt.%; the concentration of sodium alginate in the mixed solution is 0.5-6wt.%;
[0022] Preferably, the concentration of the initiator in the mixed solution is 0.1-5 wt. %; the concentration of the cross-linking agent in the mixed solution is 0-5 wt. %.
[0023] Further preferably, the concentration of the cross-linking agent in the mixed solution is 0.05-5 wt.%.
[0024] Preferably, in the vacuum impregnation in methods 1 to 2, the vacuum is released after vacuum impregnation for 1 to 5 minutes, and the cycle is repeated more than 3 times; further, the vacuum is released after vacuum impregnation for 3 to 5 minutes, and the cycle is repeated 3 to 10 times.
[0025] Preferably, the heating treatment temperature in methods 1 to 2 is 40-70° C. and the time is 2-8 hours;
[0026] Preferably, in method 2, the soaking time is 8-24 hours.
[0027] Preferably, in the method 2, the ionic liquid is at least one of calcium ion and strontium ion liquid; the concentration of the ionic liquid is 0.05-1 mol / L, and the ionic solution needs to be able to form an ionic cross-linked network with sodium alginate.
[0028] The present invention provides an application of the anisotropic wood-based cellulose dynamic adaptive hydrogel in preparing a human tissue repair material.
[0029] The present invention uses wood (such as basswood) delignification and surface modification to obtain an anisotropic oxidized cellulose framework that removes hemicellulose and lignin, and copolymerizes the cellulose framework with acrylamide (AM) and ammonium persulfate (APS) through free radical polymerization and reversible covalent bond reaction, and forms a second cross-linked structure of calcium ions and sodium alginate (SA) in the gel through ionic cross-linking. The introduction of the cellulose framework greatly improves the mechanical properties of the material and improves the stability of the material. In addition, the anisotropic cellulose framework is exposed to a larger directional channel by oxidative modification, so that the directional growth and transmission of cells and various substances can be better promoted, simulating the anisotropic structural characteristics of biological tissues. At the same time, the modification also successfully introduces aldehyde groups into the cellulose structure, and the Schiff base bond formed between the amino groups of acrylamide and the ionic bond in the second cross-linked network sodium alginate constructs a dual dynamic reversible network structure, simulating the dynamic microenvironment of biological tissues, and finally giving the material good tissue repair performance. A large number of experiments have shown that the hydrogel can simulate the dynamic microenvironment of cells while meeting the stability requirements of implant materials, and has excellent biocompatibility and tissue repair effects. In addition, the raw materials required for this method are simple and easy to obtain, the preparation method is simple and easy, the cost is low and environmentally friendly, and it is a very potential tissue repair hydrogel material, and it also provides a feasible new idea for the field of tissue repair.
[0030] Beneficial Effects
[0031] (1) The present invention provides a method for preparing anisotropic wood-based cellulose dynamic adaptive hydrogel with excellent biocompatibility and tissue repair effect, which provides a new idea for the field of tissue repair;
[0032] (2) There is no report on the construction of dynamic hydrogels by oxidative modification of wood frames. The present invention provides a new method for the synthesis of wood hydrogels and a new preparation method for the construction of dynamic hydrogels, providing a new idea for the synthesis of wood hydrogels and the construction of dynamic tissue repair bionic hydrogels.
[0033] (2) Existing covalent hydrogels are composed of static polymer networks and cannot simulate the rapidly changing microenvironment of natural ECM, allowing cells to proliferate and differentiate; however, the current dynamic adaptive hydrogels often have weak mechanical strength while maintaining good dynamic adaptability, and cannot meet the needs of long-term implantation and repair. The dynamic adaptive hydrogel constructed by modifying the cellulose framework of the present invention simulates the rapidly changing dynamic microenvironment of natural ECM by constructing a dynamic adaptive network, allowing cells to proliferate and differentiate better; at the same time, the introduction of this anisotropic cellulose skeleton can not only promote the directional growth of cells in the hydrogel network, but also solve the problem of low mechanical properties of dynamic hydrogels to a certain extent, so that the hydrogel of the present invention can meet the stability requirements of implant materials while realizing the simulation of dynamic microrings of cells, and largely solves the problem of imbalance between dynamic properties and stability of current dynamic hydrogels;
[0034] (3) The conventional method for preparing anisotropic hydrogels is relatively complicated. The present invention provides a simple and rapid method for preparing anisotropic hydrogels.
[0035] (4) The raw materials of the hydrogel prepared by the present invention are mostly derived from biomass materials, which have a wide source and are easy to obtain. This not only achieves better biocompatibility effects, but also greatly promotes the high-quality and high-value transformation of biomass materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 Comparison of infrared spectra of cellulose frameworks prepared in Example 1 and Example 4 and hydrogels prepared in Example 1, Example 2 and Example 3; wherein (a) is an infrared spectrum of cellulose framework before and after oxidation, and (b) is an infrared spectrum of hydrogel;
[0037] Figure 2 The SEM images of the cellulose frameworks prepared in Examples 1 and 4 and the hydrogel prepared in Example 1; wherein (a) the cellulose framework of Example 4 is in the radial direction, (b) the cellulose framework of Example 4 is in the longitudinal direction, (c) the oxidized cellulose framework of Example 1 is in the radial direction, (d) the oxidized cellulose framework of Example 1 is in the longitudinal direction, (e) the hydrogel of Example 1 is in the radial direction, and (f) the hydrogel of Example 1 is in the longitudinal direction;
[0038] Figure 3 The test results of mechanical properties of hydrogels prepared in Example 1 and Example 3; (a) the radial mechanical properties of hydrogels, (b) the longitudinal mechanical properties of hydrogels;
[0039] Figure 4 CCK-8 test results of the hydrogels prepared in Example 1, Example 3 and Example 4;
[0040] Figure 5The results of live and dead staining tests of hydrogel cells prepared in Example 1, Example 3 and Example 4;
[0041] Figure 6 The synthetic schematic diagram of the present invention. DETAILED DESCRIPTION
[0042] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0043] Example 1
[0044] (1) Preparation of oxidized cellulose framework: 100 g of sodium hydroxide and 50.42 g of sodium sulfite were put into a beaker, 1000 ml of ion extractor was added and stirred evenly, and then 100 g of basswood (each piece was 5 cm*5 cm*2 mm in size) was added and reacted at 100° C. for 5 h. The obtained product was repeatedly washed with deionized water three times, and then soaked with sodium hypochlorite solution until the wood turned white to obtain white wood. 2.25 g of sodium periodate was added to 50 ml of deionized water and stirred evenly, and then a piece of the white wood obtained above was added and reacted at 40° C. for 12 h, and then washed repeatedly with ethylene glycol solution (the volume ratio of ethylene glycol to water was 1:25) and deionized water twice to obtain an oxidized cellulose framework.
[0045] (2) Synthesis of anisotropic wood-based cellulose dynamic adaptive hydrogel: Take 2.5g of sodium alginate and add it to 100ml of water, stir evenly, then add 20g of acrylamide, 1g of ammonium persulfate, and 0.2g of N, N'-methylenebisacrylamide and stir evenly again, pour it into a watch glass and put in 2 pieces of the above-prepared oxidized cellulose frames, vacuum impregnate for 5 minutes and then release the vacuum, repeat the cycle six times and heat at 50°C for 5 hours to complete the cross-linking of acrylamide, then place the hydrogel in a calcium chloride solution, vacuum impregnate it six times in the same way, and continue to soak for 24 hours to obtain anisotropic wood-based cellulose dynamic adaptive hydrogel.
[0046] Example 2
[0047] (1) Preparation of oxidized cellulose framework: same as Example 1;
[0048] (2) Synthesis of anisotropic wood-based cellulose dynamic adaptive hydrogel: Take 2.5g of sodium alginate and add it to 100ml of water, stir evenly, then add 20g of acrylamide, 1g of ammonium persulfate, and 0.2g of N, N'-methylenebisacrylamide and stir evenly again, pour it into a watch glass and put in 2 pieces of the above-prepared oxidized cellulose frames, vacuum immerse for 5 minutes and then release the vacuum, repeat the cycle six times and heat at 50°C for 5 hours to completely cross-link the acrylamide, thereby obtaining anisotropic wood-based cellulose dynamic adaptive hydrogel.
[0049] Example 3
[0050] (1) Preparation of oxidized cellulose framework: same as Example 1;
[0051] (2) Synthesis of anisotropic wood-based cellulose dynamic adaptive hydrogel: Take 20g acrylamide, 1g ammonium persulfate, and 0.2g N, N'-methylenebispropionamide and add them to 100ml water. After stirring evenly, pour it into a watch glass and put in 2 pieces of the above-prepared oxidized cellulose frames. After vacuum impregnation for 5 minutes, release the vacuum, repeat the cycle six times, and heat at 50°C for 5 hours to completely cross-link the acrylamide to obtain anisotropic wood-based cellulose dynamic adaptive hydrogel.
[0052] Example 4
[0053] (1) Preparation of cellulose framework: 100 g of sodium hydroxide and 50.42 g of sodium sulfite were placed in a beaker, 1000 ml of ion extractant was added and stirred evenly, and then 100 g of basswood (each piece was 5 cm*5 cm*2 mm in size) was added and reacted at 100° C. for 5 h. The obtained product was repeatedly washed with deionized water three times, and then soaked in sodium hypochlorite solution until the wood turned white to obtain a cellulose framework;
[0054] (2) Synthesis of anisotropic wood-based cellulose hydrogel: 2.5 g of sodium alginate was added to 100 ml of water and stirred evenly. Then, 20 g of acrylamide, 1 g of ammonium persulfate, and 0.2 g of N, N'-methylenebispropionamide were added and stirred evenly again. Then, the mixture was poured into a watch glass and two pieces of the cellulose frames prepared above were placed therein. The mixture was vacuum impregnated for 5 minutes and then released. After six reciprocating cycles, the mixture was heated at 50°C for 5 hours to completely crosslink the acrylamide. The hydrogel was then placed in a calcium chloride solution and vacuum impregnated six times in the same manner. The mixture was then soaked for 24 hours to obtain anisotropic wood-based cellulose hydrogel.
[0055] (I) Product structure and performance characterization
[0056] The structure and properties of the anisotropic wood-based cellulose dynamic adaptive hydrogel of the present invention are described below by infrared spectroscopy, scanning electron microscopy, and mechanical property testing.
[0057] 1. Infrared spectroscopy (FTIR)
[0058] Figure 1 (a) is the infrared spectra of cellulose framework before and after modification. Compared with the white wood cellulose framework, the oxidized cellulose framework has a peak at 880 cm -1 and 1730cm -1 The presence of characteristic peaks of hemiacetal and hydrated forms and aldehyde groups (C=O) indicates the successful modification of the cellulose framework, which greatly facilitates the formation of the subsequent dynamic gel structure between the gel components and the cellulose framework; Figure 1 (b) is the infrared spectra of the hydrogels of Example 1, Example 2, and Example 3. Compared with Example 2, the carboxyl peak of sodium alginate in Example 1 increases from 1413 cm -1 Move to 1423cm -1 , indicating that sodium alginate and calcium ions are successfully cross-linked; compared with Example 3, Example 1 has a -1 The strong broadbands at 1610 and 1668 cm indicate that the lone pair electrons on the N atom of PAM form strong intermolecular hydrogen bonds with the H atoms of alginate. -1 They correspond to -C=N- and -C=C- stretching vibrations, respectively, indicating the formation of reversible Schiff base between PAM and modified wood. Based on the above analysis, it is believed that the anisotropic dynamic hydrogel of cellulose was successfully synthesized.
[0059] 2. Scanning electron microscope (SEM)
[0060] Figure 2 (ad) are scanning electron micrographs of the cellulose framework before and after modification. Compared with unoxidized wood, the thinning of the cellulose structure leads to larger voids on the surface of the cellulose framework, which greatly promotes the penetration of gel components and their combination with the cellulose framework. The larger void channel structure is also more conducive to the physiological activities of cells. Figure 2 (ef) is a scanning electron micrograph of the hydrogel of Example 1, and the surface gel material evenly enters the wood structure and forms a good bond with the oxidized cellulose framework after gelation. Based on the above analysis, it is believed that the anisotropic dynamic cellulose hydrogel is successfully synthesized.
[0061] 3. Mechanical properties test
[0062] Test steps: The gels of Example 1 and Example 3 were soaked in deionized water for 24 hours and then cut into hydrogel blocks of similar length (length 0.8-1.5 cm, width 0.3-0.6 mm), and tested using a universal mechanical testing machine (tensile rate 50 mm / min).
[0063] like Figure 3The mechanical properties of Example 1 and Example 3 along the radial (R direction) and longitudinal (L direction) directions of the hydrogel are shown. The radial fracture strength, elastic modulus, and elongation at break of Example 3 can reach 0.272MPa, 2.74MPa, and 10.889%, and the longitudinal fracture strength, elastic modulus, and elongation at break can reach 0.43MPa, 4.65MPa, and 14.86%. This mechanical property is much higher than that of pure acrylamide hydrogel, so the hydrogel performance is greatly improved after the introduction of the modified cellulose framework. Compared with Example 3, the radial fracture strength, elastic modulus, and elongation at break of Example 1 after the introduction of the ion cross-linked network reach 0.42MPa, 3.061MPa, and 13.86%, and the longitudinal fracture strength, elastic modulus, and elongation at break reach 0.58MPa, 4.77MPa, and 15.37%. Therefore, after the introduction of the double network, the mechanical properties are improved, which can meet the needs of transplantation and initial growth, and achieve a balance between the dynamic properties and stability of the dynamic hydrogel.
[0064] (II) Product biocompatibility characterization
[0065] The biocompatibility of the anisotropic wood-based cellulose dynamic adaptive hydrogel of the present invention is described below by CCK-8 and cell live-dead staining tests.
[0066] Test steps:
[0067] (1) Prepare the extract: soak and wash Example 1, Example 3, and Example 4 in deionized water for 3 days (change deionized water every 6 hours), then place them in a 12-well plate and wash them 3 times with 75% ethanol and phosphate buffered saline (PBS) (30 minutes each time), then place them in a centrifuge tube and soak them in αMEM culture medium for 24 hours. Then add the αMEM culture medium of the soaked materials to the cells for resuspending and counting, then drop them into 96-well plates and 24-well plates and culture them for 1, 3, and 5 days respectively;
[0068] (2) CCK-8 test: After the culture medium in the 96-well plate described in (1) was aspirated, 100 ul of CCK-8 staining solution was added to each well and cultured in an incubator for 60 min before performing the CCK-8 test;
[0069] (3) Cell live and dead staining: The culture medium in the 24-well plate described in (1) was aspirated and centrifuged, and the supernatant was removed. PBS was added and live and dead staining agents were added in proportion. 1000 ul of cell live and dead staining solution was added to each well and cultured for 15 min. The staining solution was collected and centrifuged, the supernatant was removed, and PBS was added to resuspend it. After that, 100 ul of the solution was added to each well to terminate the staining, and the live and dead conditions of the cells were observed using a fluorescence microscope;
[0070] The ratio of the hydrogel to αMEM described in (1) is 10 mg / ml;
[0071] The amount of cells used for CCK-8 and live-dead staining in the cell solution described in (1) is: 3000 / well and 10000 / well, and the cells used are MC3T3;
[0072] The volume ratio of DMEM to CCK-8 staining agent in the CCK-8 staining solution described in (2) is 9:1;
[0073] The volume ratio of PBS, live cell stain and dead cell stain in the cell live and dead stain solution described in (3) is 2000:1:1.
[0074] Test results:
[0075] (1) CCK-8 test
[0076] Figure 4 The results show that the cck-8 results of Example 1, Example 3, and Example 4 all show an upward trend, among which Example 1 has the most obvious upward trend and the highest CCK-8 value, proving its best biocompatibility.
[0077] (2) Cell live and dead staining
[0078] The hydrogel cell morphology of Example 1 is the best, and the cell quantity increases with the increase of culture days. The cells and cell quantity of Example 3 are second, and the morphology of Example 4 is poor and the cell quantity is also small, which proves that the cellulose hydrogel synthesized in this scheme has good biocompatibility.
[0079] In summary, compared with Example 4, the materials in Examples 1 and 3 showed better cell compatibility after the introduction of the dynamic network, which confirms the theory that the dynamic network is beneficial to the physiological activities of cells and thus promotes cell growth; in addition, after the introduction of the ion network in Example 1, the cell compatibility was further improved and the cells in the gel also showed better cell morphology. This shows that the introduction of the ion network can not only increase the mechanical properties of the material, give the dynamic hydrogel excellent stability, and achieve dynamic and static synergistic interactions, but also further promote cell growth, thereby achieving better tissue repair effects.
Claims
1. An anisotropic wood-based cellulose dynamic adaptive hydrogel, characterized in that: The anisotropic wood-based cellulose dynamic adaptive hydrogel component includes an oxidized cellulose framework and acrylamide, and reacts to form a chemical and reversible cross-linked network; or the anisotropic wood-based cellulose dynamic adaptive hydrogel component includes an oxidized cellulose framework, acrylamide, and sodium alginate, wherein the hydrogel contains an oxidized cellulose framework, acrylamide reacts to form a chemical and reversible cross-linked network, and the sodium alginate forms a second heavy ion dynamic cross-linked network through ionic cross-linking.
2. A method for preparing anisotropic wood-based cellulose dynamic adaptive hydrogel, comprising method 1 or method 2: Method 1: A gel precursor containing amino groups, an initiator, and water are mixed to obtain a mixed solution, an oxidized cellulose framework is added, and then vacuum impregnation and heating treatment are performed to obtain an anisotropic wood-based cellulose dynamic adaptive hydrogel, wherein the gel precursor containing amino groups is acrylamide; Method 2: A gel precursor containing amino groups, an initiator, and sodium alginate are mixed to obtain a mixed solution, an oxidized cellulose framework is added, and then vacuum impregnated and heated, and then vacuum impregnated and soaked in an ionic solution to obtain an anisotropic wood-based cellulose dynamic adaptive hydrogel, wherein the gel precursor containing amino groups is acrylamide.
3. The preparation method according to claim 2, characterized in that: The preparation method of the oxidized cellulose framework in methods 1 to 2 comprises: reacting wood in a mixed solution of sodium hydroxide and sodium sulfite, washing, then soaking in a sodium hypochlorite solution until the wood turns white to obtain white wood, and placing the white wood in a sodium periodate solution to react and wash to obtain the oxidized cellulose framework.
4. The preparation method according to claim 3, characterized in that: The wood material comprises at least one of basswood and balsa wood; the concentration of sodium hydroxide in the mixed solution of sodium hydroxide and sodium sulfite is 1-5 mol / L, and the concentration of sodium sulfite is 0.1-1.5 mol / L; the mass ratio of the mixed solution to the wood material is 100:5-20; the mass percentage concentration of the sodium periodate solution is 0.5-5wt.%.
5. The preparation method according to claim 3, characterized in that: The wood is reacted and washed in a mixed solution of sodium hydroxide and sodium sulfite, wherein the reaction temperature is 85-100° C. and the time is 3-5 hours; the washing is performed with deionized water; The white wood is placed in a sodium periodate solution for reaction and washing, wherein the reaction temperature is 20-50° C. and the time is 3-12 hours; the washing is performed using ethylene glycol and deionized water.
6. The preparation method according to claim 2, characterized in that: In the method 1 and the method 2, the initiator includes at least one of ammonium persulfate and Irgacure 2959; the mixed solution also includes a crosslinking agent, wherein the crosslinking agent includes at least one of N, N'-methylenebispropionamide and polyisomethacrylate; The concentration of acrylamide in the mixed solution is 10-40wt.%; The concentration of sodium alginate in the mixed solution is 0.5-6wt.%; The concentration of the initiator in the mixed solution is 0.1-5wt.%; The concentration of the cross-linking agent in the mixed solution is 0-5 wt.%.
7. The preparation method according to claim 2, characterized in that: Vacuum impregnation as described in methods 1 to 2: release the vacuum after vacuum impregnation for 1 to 5 minutes, and repeat for more than 3 times; In methods 1 and 2, the heating treatment temperature is 40-70°C and the time is 2-8h; In method 2, the soaking time is 8-24 hours.
8. The preparation method according to claim 2, characterized in that: In the method 2, the ionic liquid is at least one of calcium ion and strontium ion liquid; and the concentration of the ionic liquid is 0.05-1 mol / L.
9. Use of the anisotropic wood-based cellulose dynamic adaptive hydrogel according to claim 1 in preparing human tissue repair materials.